Hypertrophic pyloric stenosis treated with co-administration of nitroglycerin and atropine sulfate - Yoko Shino; Masaaki Doi; Yasuko Furuichi; Hiroshi Nakai; Seiji Kinoshita (Elsevier, 2018)
Hypertrophic pyloric stenosis (HPS) is a common infantile disease that causes a transit pyloric disorder. For the treatment of this disorder, intravenous atropine sulfate (AS) has been reported to be effective. However, AS treatment is ineffective in some cases, and these cases require surgical treatment. Recently, it has been reported that the co-administration of nitroglycerin (NTG) and AS is more effective than the administration of AS alone. Herein, we present two cases of infants with HPS treated using percutaneous NTG along with intravenous AS. Both cases were refractory to intravenous AS alone. After additional administrations of percutaneous NTG, their vomiting was rapidly resolved. These cases highlight the effectiveness of the co-administration of NTG and AS for HPS. Keywords: Hypertrophic pyloric stenosis, Nitroglycerin, Atropine sulfate, Infant